A Rose by Any Other Verb: The Effect of Expectations and Word Category on Processing Effort in Situated Sentence Comprehension - Sikos, Les; Stein, Katharina; Staudte, Maria (Frontiers in Psychology, 2021)
Recent work has shown that linguistic and visual contexts jointly modulate linguistic expectancy and, thus, the processing effort for a (more or less) expected critical word (Ankener et al., 2018; Tourtouri et al., 2019; Staudte et al., 2020). According to these findings, uncertainty about the upcoming referent in a visually-situated sentence can be reduced by exploiting the selectional restrictions of a preceding word (e.g., a verb or an adjective), which then reduces processing effort on the critical word (e.g., a referential noun). Interestingly, however, no such modulation was observed in these studies on the expectation-generating word itself. The goal of the current study is to investigate whether the reduction of uncertainty (i.e., the generation of expectations) simply does not modulate processing effort — or whether the particular subject-verb-object (SVO) sentence structure used in these studies (which emphasizes the referential nature of the noun as direct pointer to visually co-present objects) accounts for the observed pattern. To test these questions, the current design reverses the functional roles of nouns and verbs by using sentence constructions in which the noun reduces uncertainty about upcoming verbs, and the verb provides the disambiguating and reference-resolving piece of information. Experiment 1 (a Visual World Paradigm study) and Experiment 2 (a Grammaticality Maze study) both replicate the effect found in Ankener et al. (2018) of visually-situated context on the word which uniquely identifies the referent, albeit on the verb in the current study. Results on the noun, where uncertainty is reduced and expectations are generated in the current design, were mixed and were most likely influenced by design decisions specific to each experiment. These results show that processing of the reference-resolving word — whether it be a noun or a verb — reliably benefits from the prior linguistic and visual information that lead to the generation of concrete expectations.